Delimiting Cantheconidea Schouteden 1907, with the description of a new genus (Heteroptera: Pentatomidae: Asopinae) - Ricardo Brugnera; Jocelia Grazia; Andrew Maynard; Marcos Roca-Cusachs (European Journal of Taxonomy, 2024)
Among the 44 genera of predatory stink bugs (Asopinae) described for the Old World, there is a notable lack of recent studies. In this research, we aim to fill this gap by investigating the taxonomic history and morphology of species of Cantheconidea. As results, we present the redescription of the genus and validate three species: C. humeralis, C. javana and C. mitis comb. nov. A lectotype for C. mitis is designated and comments on the type material are given. Additionally, we transfer four species from Cantheconidea to the genus Eocanthecona: E. acuta comb. nov., E. variabilis comb. nov., E. gaugleri comb. nov. and E. insularis comb. nov. To accommodate the unique characteristics of Cantheconidea cyanacantha, we describe a new genus, Cantheconesia Brugnera & Roca-Cusachs gen. nov., and transfer the species, resulting in Cantheconesia cyanacantha gen. et comb. nov. Our study provides detailed redescriptions of species and accompanying images to support taxonomic decisions and presents new distribution records.